Actinomyces Acute Rhinosinusitis Complicated by Subperiosteal Abscess in an Immunocompromised 12-Year-Old: Case Report and Literature Review - Sai V. Nimmagadda; Li-Xing Man; Margo K. McKenna; John J. Faria; Isaac L. Schmale (Case Reports in Otolaryngology)
Objective. To describe a rare case of pediatric actinomycotic rhinosinusitis with orbital subperiosteal abscess and review the current literature to assess methods of diagnosis, treatment modalities, and outcomes with appropriate treatment. Methods. A case report and a review of the literature. Results. A 12-year-old patient with Crohn’s disease on infliximab presented with rhinosinusitis with orbital subperiosteal abscess formation. Endoscopic sinus surgery was performed and cultures grew actinomyces. A prolonged course of antibiotics was started, resulting in the complete resolution of the infection. In a literature review, all cases of uncomplicated and complicated actinomyces rhinosinusitis managed with appropriate surgery and prolonged antibiotics resulted in a cure. Our case is the first reported in a pediatric patient and the first taking immunosuppressive medication. Overall, only 3 cases of actinomyces rhinosinusitis in immunosuppressed individuals have been reported, each with uncontrolled diabetes and each also responded well to surgery and appropriate antibiotics. Conclusion. Actinomycosis of the paranasal sinuses poses a diagnostic challenge, with infections varying widely in presentation and extent of disease. A high index of suspicion, appropriate testing, and early aggressive treatment are critical in managing patients with this infection. Our case and prior published studies show that actinomyces rhinosinusitis can be successfully managed with endoscopic sinus surgery, abscess drainage as necessary, and a prolonged course of antibiotics, even in immunocompromised and pediatric populations.